Optimization Technique Approach on a Two-Stroke Engine with Coated Piston and Gasoline Blends - Kiran, AVNS; Prasad, T Hari (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 8 No 3&4 (2021): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The performance and emissions affected by the coating have been analyzed in this study. In the present experimental investigation with gasoline blends of butanol and propanol along with magnesium partially stabilized zirconium (Mg-PSZ) as thermal barrier coating on piston crown of 100 microns. The samples of gasoline blends were blended with petrol in 20:80 ratios (20% of ethanol and 80% of gasoline, 20% of butanol and 80% of gasoline). The specific standard parameters have been modified with Mg-PSZ coated petrol engine with aid of design of experiment by Taguchi with grey relational analysis optimisation method, for improving the engine performance and emission reduction. The result shows that modified Mg-PSZ coated piston at B20. Finally, the results of the experiments were compared with uncoated and coated engine and optimised parameters have been identified for Mg-PSZ coated modified piston using Taguchi grey relational method. How to cite this article:  AVNS Kiran, T Hari Prasad. Optimization Technique Approach on a Two-Stroke Engine with Coated Piston and Gasoline Blends. J Adv Res Alt Energ Env Eco 2021; 8(3&4): 6-14.